A simple device to measure bend limit of sheet metals. Issue 1 (November 2020) - Deole, A; Etxebarria, N; Mendiguren, J; Ilinich, A; Weiss, M
Abstract: The analysis of bend fracture limits of sheet metals is important for the automotive industry. For high and mid-ductility materials, current methods are often unreliable due to the difficultly of detecting the initiation of a crack on the outer surface of the bend. Sophisticated techniques that rely on the strain evolution in the material are capable to detect the cracks and establish the bend limits using d igital i mage c orrelation (DIC) strain measurement systems. However, these techniques are complex and sometimes impractical for industrial use. This study uses a simplified bend test technique that uses optical image processing to detect crack initiation to then determine the bend limits of aluminum alloys using a m odified a ngled line m ethod (MALM). The findings of this study indicate that the optical method is inconsistent in detecting the crack initiation and likely to result in a large deviation in detected the bend limits.